Ocular metastasis in a patient with squamous cell carcinoma tongue: A rare case - Nagalakshmi Narayana-Swamy; Alhaj Farhath Tasneem (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
Ophthalmic metastasis from an extraocular primary malignancy is a rare event. Tongue is the most common primary site after hypo-pharynx among the oral malignancies causing distant metastasis [1].